DEVELOPMENT OF PEDESTRIAN INFRASTRUCTURE AROUND THE TOD AREA TO ENCOUNTER LIFE AFTER COVID-19 PANDEMIC (CASE STUDY: DUKUH ATAS AND LEBAK BULUS TOD AREA) - Fitria Trinanda, Rizka
The TOD concept was developed by integrating land use and transportation by providing high density and mixed-used areas around transit nodes through easy connectivity by walking and cycling. Activity concentration around the nodes could be a weakness after Covid-19 pandemic. The pandemic, which encourage physical distancing makes space resources important in the TOD Area. Interventions in the secondary corridors of TOD Areas, such as sidewalks, are important to increase the flexibility and resilience of the entire network. This study aims to formulate the recommendations for the development to encounter life after Covid-19 pandemic. The research was conducted by standardizing the development of pedestrian paths in the TOD area after the Covid-19 pandemic in Indonesia. To achieve the objectives, datas were collected through observation and comparison questionnaire by using AHP analysis to determine the weight of standards that were made, and descriptive qualitative analysis, spatial analysis, and infrastructure readiness analysis to determine the readiness of the existing pedestrian infrastructure in the case study location. The result of the study shows that the readiness in terms of physical infrastructure around the Dukuh Atas TOD area is on a receptive scale with a value of 62% and the Lebak Bulus TOD area is on a ready scale with a value of 54% and the readiness in terms of policy is on a ready scale with a value of 52.3%. This value means that pedestrian infrastructure and policies are receptive/ready to support life after the Covid-19 pandemic but are still experiencing problems in their implementation. Recommendations from this research are the acceleration of sidewalk revitalization and the formation of sidewalk master plan so that the sustainable of sidewalk development can continues, as well as the implementation of policies that benefit pedestrians such as widening the emergency pedestrian lanes.